Implementation Of Democratic Leadership Style In The Central Surgical Installation At Latemmamala Hospital, Soppeng - Surianti Surianti; Nur Fitriana Ramadhani; Salsabila Nurwanti; Indra Jaya Pratama; Aldi Aldi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This Community Service project focused on the implementation of a democratic leadership style in the Central Surgical Installation of Latemmamala Hospital, Soppeng. The central objective of this activity was to measure the effect of democratic leadership, where staff input and suggestions are listened to and valued, on key variables such as nurse discipline and performance. The target group was staff in the Central Surgical Installation of Latemmamala Hospital, who were experiencing a decline in trust in their leaders due to their perceived inability to provide firm leadership. The methods used included monitoring interactions and interviews with the head of staff of the Central Surgical Installation, as well as direct observation of the actual situation in the hospital. Overall, this activity concluded that a democratic leadership style has proven highly effective in a high-risk clinical environment such as the Central Surgical Installation. The results showed a significant and strong relationship between this leadership model and improved performance quality and discipline of all nurses. In other words, involving staff in the managerial process is key to successfully optimizing the responsibility and professionalism of the surgical team